The ecology of agricultural ecosystems : long-term research on the path to sustainability - Hamilton, Stephen K. (Long-Term Ecological Research Network series., 2015)
Evidence has been mounting for some time that intensive row-crop agriculture as practiced in developed countries may not be environmentally sustainable, with concerns increasingly being raised about climate change, implications for water quantity and quality, and soil degradation. This volume synthesizes two decades of research on the sustainability of temperate, row-crop ecosystems of the Midwestern United States. The overarching hypothesis guiding this work has been that more biologically based management practices could greatly reduce negative impacts while maintaining sufficient productivi.